Kropotkin and the rise of revolutionary anarchism, 1872-1886 - Cahm, Caroline (Cambridge University Press, 1989)
This major study of Peter Kropotkin sets him firmly in the context of the development of the European anarchist movement as the man who became, after Bakunin's death, their chief exponent of anarchist ideas. It traces the origins and development of his ideas and revolutionary practice from 1872 to 1886, and assesses the subsequent influence of his life and work upon European radical and socialist movements. Dr Cahm analyses Kropotkin's role in the transformation of Bakunin's anti-authoritarian socialism, and shows how two principal types of revolutionary action emerge from anarchist efforts to develop clear alternatives to the parliamentary strategies of social democrats; one based on the activity of individuals and small groups, the other related to large-scale collective action